Biomassa e Biogás da Suinocultura - Fernandes, Dangela Maria (2012)
The intensive pig farming's development promoted the production of residual biomass large amounts, when improperly handled becomes a major environment s pollution sources. Therefore, waste management should be seen as an integral part of system's production pigs and should be included in planning this activity. In this context, aiming to evaluate the residual biomass' management generated in the production system for finishing pigs, Unit Colombari farm, there was a study about the water consumption, feed consumption and residues production during the period October 2010 to February 2011 with the goal of generating productivity indices related to the productive system The gotten results indicated that the rates for the daily water consumption per pig ranged from 1.2 to 2.4 liters, the daily feed intake per animal was 1.90 kg and the manure's daily production per animal appeared in 7.3 liters. It is considered that the productive unit is fitted in an efficient handling characteristic, having efficacy in reducing water consumption in the parameterization of the animal feed and residual biomass' control.